Mahalia Mouse goes to college [compact disc, unabridged] - Lithgow, John, 1945- (Simon & Schuster Books for Young Readers, 2007)
Sent by her parents to find food, Mahalia Mouse finds herself trapped in a backpack and transported to a physics classroom at Harvard University, where she discovers an aptitude for science.